PENGARUH KEMUDAHAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PENGGUNA GOPAY - Wildan Yusufi, (2023)
The purpose of this study is to examine the effect of convenience and promotions on purchasing decisions of Gopay users. This study uses a quantitative methodology and data analysis techniques multiple linear regression. The population in this study were UPN "Veteran" Jakarta students majoring in Management with the respondent criteria 1) The sample was limited to the UPNVJ student environment; 2) Respondents have transacted using Gopay at least 1 time. The number of samples used in this study were 50 respondents. The data in this study were obtained directly from filling out a questionnaire (questionnaire) given to respondents in the form of a Google form which would then be answered by respondents. The data analysis technique used in this study is descriptive analysis, classical assumption test and multiple linear regression data analysis. The results of this study found that convenience and promotion had a positive and significant effect on purchasing decisions of Gopay users.